Altered gut microbiota is associated with different immunologic responses to antiretroviral therapy in HIV‐infected men who have sex with men. Issue 3 (23rd March 2023) - Zhao, Heping; Feng, Anping; Luo, Dan; Wu, Hao; Zhang, Ge; Zhang, Lin; Yuan, Jinqiu; Lin, Yi‐Fan; Li, Linghua; Zou, Huachun
Abstract: The association between gut microbiota and immunologic nonresponse among people living with HIV (PLHIV) on antiretroviral therapy (ART) is not well documented. This study aimed to characterize gut microbiota among HIV‐infected men who have sex with men (MSM) with different immunologic responses. We recruited HIV‐infected MSM and HIV‐uninfected MSM (healthy controls, HC) in Guangzhou, June–October 2021. HIV‐infected MSM were grouped into good immunological responders (GIR) (CD4 + T cell count ≥ 350 cells/μL) and poor immunological responders (PIR) (<350 cells/μL). Blood and stool samples were collected. Microbial translocation in serum was performed using enzyme‐linked immunosorbent assay (ELISA). Bacterial 16S ribosomal DNA sequencing was performed on stool samples, and microbial metabolites were obtained through gas chromatography‐mass spectrometry. 56 GIR, 41 PIR, and 51 HC were included. Microbial translocation marker soluble cluster of differentiation 14 (sCD14) in both GIR and PIR groups was significantly higher than that in HC. Compared with PIR or HC groups, the genera of Coprococcus, Blautia, Clostridium, and SMB53 were decreased, whereas Megamonas and Megasphaera were more abundant in GIR group. Compared with GIR or PIR groups, Bifidobacterium, Collinsella, Faecalibacterium, Oscillospira, and Roseburia were more abundant, whereas Escherichia was decreased in HC group. The levels of benzenoids, imidazoles, phenylpropanoic acids, phenylpropanoids, and pyridines showed strongly significant correlations between differential genera. This study presented a comprehensive landscape of gut microbiota in PLHIV with different treatment outcomes. Megamonas, Coprococcus and Blautia were the major genera correlated with different immunologic responses in PLHIV.